Prolonged grief disorder in Arabic-speaking treatment-seeking populations: Relationship with socio-demographic aspects, loss- and trauma-related characteristics, and mental health support - Specht, Freya; Vöhringer, Max; Knaevelsrud, Christine; Wagner, Birgit; Stammel, Nadine; Böttche, Maria (Frontiers in Psychiatry, 2022)
Introduction. Prolonged grief disorder (PGD) has been included as a new diagnosis in the ICD-11 and is set to be included in the DSM-5-TR. To better identify vulnerable individuals, different factors associated with PGD have to be taken into account, but results regarding these factors remain equivocal. Moreover, few studies on PGD are available from Arabic-speaking populations and from different countries dealing with conflicts and wars. The objective was thus to examine PGD prevalence and associated characteristics in these populations. Materials and Method. A total of N = 1,051 bereaved participants from Arabic-speaking populations completed the PG-13 as part of a screening procedure for an online mental health intervention. Multiple linear regression was conducted to examine associated factors for PGD symptom severity, and multiple logistic regression was applied to investigate associated factors for PGD according to PG-13 diagnostic criteria. Results. Of the participants, 18.8% (n = 198) met the PGD diagnostic criteria, at an average of about six years post-loss. The multiple linear regression yielded eight associated factors for PGD symptom severity (age, gender, number of losses, number of traumatic event types, relationship with the deceased, age at loss, impairment during first year post-loss, perceived social support), which explained 40.2% of the variance (F(17, 1033) = 40.82, p < 0.001, R2 = .402). The multiple logistic regression yielded five significant associations with PGD (gender, relationship with the deceased, number of lost persons, impairment during first year post-loss, perceived social support), which explained 33.0% (Nagelkerke R2) of the variance in PGD according to PG-13 diagnostic criteria. Discussion. A substantial proportion of the participants met the PG-13 criteria for PGD, emphasizing that therapeutic services are indispensable in this population. The associated factors for PGD found in our Arab-speaking sample are largely consistent with those found in studies from other regions. The slightly differing numbers of associated factors between the linear and logistic regression underline that a continuous score reflects the continuum between normal and dysfunctional grieving, and therefore also a range of factors associated with PGD.